2022
DOI: 10.1021/acsomega.2c04512
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Waste Toner Powder into Valuable Fe2O3 Nanoparticles for the Preparation of Recyclable Co(II)-NH2-SiO2@Fe2O3 and Its Applications in the Synthesis of Polyhydroquinoline and Quinazoline Derivatives

Abstract: Ecological recycling of waste materials by converting them into valuable nanomaterials can be considered a great opportunity for management and fortification of the environment. This article deals with the environment-friendly synthesis of Fe2O3 nanoparticles (composed of α-Fe2O3 and γ-Fe2O3) using waste toner powder (WTP) via calcination. Fe2O3 nanoparticles were then coated with silica using TEOS, functionalized with silane (APTMS), and immobilized with Co­(II) to get the desired biocompatible and cost-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“… Precursor Synthesis procedure Final Product Crystallite size (nm) Ms (emu/g) Hc (Oe) Application Ref. Scrap iron Hydrothermal γ-Fe 2 O 3 nanoparticles 20 to 40 0.3813 10 Environmental waste management [ 1 ] Iron pentacarbonyl, Fe(CO) 5 Microwave plasma synthesis γ-Fe 2 O 3 nanoparticles 2 to ∼50 13.2–67.6 Impact of size reduction [ 7 ] Slag, mill scale, scrap and iron dust Co-precipitation γ-Fe 2 O 3 particles 11.04 to 18.62 17.44–41.69 3.464–60.193 Waste disposal problem [ 42 ] Waste Toner Powder Thermal transformation technique Magnetic iron oxide nanoparticles 32.07 19.5 Preparation of Recyclable Co(II)– NH 2 –SiO 2 @Fe 2 O 3 [ 69 ] Iron chloride and urea Co-precipitation γ-Fe 2 O 3 nanoparticles 60 0.025 1250 Removal of toxic heavy metals from electroplating wastewater [ 70 ] Recyclable electro-coagulated sludge …”
Section: Resultsmentioning
confidence: 99%
“… Precursor Synthesis procedure Final Product Crystallite size (nm) Ms (emu/g) Hc (Oe) Application Ref. Scrap iron Hydrothermal γ-Fe 2 O 3 nanoparticles 20 to 40 0.3813 10 Environmental waste management [ 1 ] Iron pentacarbonyl, Fe(CO) 5 Microwave plasma synthesis γ-Fe 2 O 3 nanoparticles 2 to ∼50 13.2–67.6 Impact of size reduction [ 7 ] Slag, mill scale, scrap and iron dust Co-precipitation γ-Fe 2 O 3 particles 11.04 to 18.62 17.44–41.69 3.464–60.193 Waste disposal problem [ 42 ] Waste Toner Powder Thermal transformation technique Magnetic iron oxide nanoparticles 32.07 19.5 Preparation of Recyclable Co(II)– NH 2 –SiO 2 @Fe 2 O 3 [ 69 ] Iron chloride and urea Co-precipitation γ-Fe 2 O 3 nanoparticles 60 0.025 1250 Removal of toxic heavy metals from electroplating wastewater [ 70 ] Recyclable electro-coagulated sludge …”
Section: Resultsmentioning
confidence: 99%
“…Beller et al focussed on synthesising novel heterogeneous NiNPs and demonstrated their catalytic and effective use as catalysts for the hydrogenation of quinolines (101), isoquinolines (103), indole (105), and 1,10-phenanthroline (107) to give the corresponding tetrahydro derivatives (102/104/106/108; Scheme 30). 83 These NiNPs were synthesised from silica, nickel acetate and 1,10-phenanthroline followed by pyrolysis at 800 °C under argon medium.…”
Section: Ninpsmentioning
confidence: 99%
“…Gupta et al synthesised polyhydroquinolones using Co(II)-NH 2 -SiO 2 @Fe 2 O 3 NPs as the catalyst (Scheme 48). 101 The authors attempted the transformation of waste toner powder into recyclable NPs and analysed their applications for the synthesis of these heterocycles. Fe 2 O 3 NPs were formed via calcination, functionalised with silane and coated with silica followed by their immobilisation using Co(II) salts.…”
Section: Scheme 47 Cufe 2 O 4 Np Catalysed Annulation Of 151 With 152mentioning
confidence: 99%
“…Nanocatalysis acts as bridge between homogeneous and heterogeneous catalyst. 4 Both homogeneous and heterogeneous catalysts are combined when catalytic support is added to nanocatalyst. In Chemistry, a catalyst support is a material, usually a solid with a high surface area, to which a catalyst is affixed.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocatalysis opens up a number of opportunities in sustainable and Green chemistry because it lessens the amount of waste, usage of potentially harmful chemicals and energy consumption connected with a chemical process. Nanocatalysis acts as bridge between homogeneous and heterogeneous catalyst 4 . Both homogeneous and heterogeneous catalysts are combined when catalytic support is added to nanocatalyst.…”
Section: Introductionmentioning
confidence: 99%